DESIGN EXPLORATION AS A RESEARCH DISCOVERY PHASE THROUGH GRAPHIC DESIGN JOB ADVERTISING - Sugiarto Sugiarto; Santi Widiastuti (STEKOM PRESS, 2021)
Main Objective: This study explores the work vacancy advertising for graphic designers in some countries and appraises differences in economic, and educational infrastructure. Background problem: The designer's role is changing and building a more critical advancement to the organization. The job and expertise of a graphic designer as commonly associated with boundless visual results, equally designing for flyers and having knowledge of typography and visual content. Apart from that, graphic designers job and competent in equal employment, study, and technology. The expansive work and skill set of graphic designers mien a challenge for lecturers and professionals alike to carry abreast of the work of graphic designers. Novelty: For design professionals and lecturers, employment provides an intermediary for compassionate labor advertising which can format academic activities and self-improvement intentions. In design research, job Ads bring information about the competencies demanded by employers in the design professional field as well as about the organization's level of knowledge of the profession. Research Method: This study uses the doc analysis method in traditional and digital graphic design job advertisements to investigate the skills that organizations seek when recruiting graphic designers. Finding/Result: The job and skills of a graphic designer are more expansive than repeatedly characterized. Graphic designers primarily provide digital and print jobs. Graphic designers primarily provide digital and print jobs. To do this kind of job, a graphic designer must have not only visual design experiences but also experiences generally identical with other areas, equally “business”, “project management”, and “research”. Conclusion: The results of this study indicate that job advertisements reverse the former during interpretive job advancement for graphic designers in the future. As a suggestion for investigating future professional development, design researchers should make more careful use of the opportunity and scope contributed by job advertisements. Keywords: Job Advertisement, Graphic design, Graphic Designer